Prevalence and predictors of virological failure among the people living with HIV on antiretroviral treatment in East Africa: evidence from a systematic review with meta-analysis and meta-regression of published studies from 2016 to 2023 - Maria Magdalene Namaganda; Hussein Mukasa Kafeero; Joyce Nakatumba Nabende; David Patrick Kateete; Charles Batte; Misaki Wanyengera; Daudi Jjingo; Moses Joloba; Florence Kivunike; Isaac Ssewanyana; Yunus Miya; Darius Kato; et al. (HIV Research & Clinical Practice)
Background Virological failure (VF) significantly threatens the efficacy of antiretroviral therapy (ART) programs in East Africa. This systematic review and meta-analysis assess the prevalence and predictors of VF among individuals living with HIV. Methods We searched PubMed, Web of Science, African Journals Online, and EMBASE for relevant studies. Heterogeneity was assessed using the I2 statistic, and random-effects models addressed between-study variability. Publication bias was examined through funnel plots, Egger’s regression, and Begg’s tests. Subgroup analyses and meta-regression explored heterogeneity sources and potential VF predictors. Analyses were conducted using MedCalc version 20.010, adhering to PRISMA 2020 guidelines. Results Twenty-five records were included, with a sample size of 29,829 people living with HIV on ART. The pooled prevalence of VF in East Africa was 19.4% (95% CI: 15.2%–24.0%), with substantial heterogeneity across studies. Sociodemographic predictors of VF included male sex (30.9%, p < .001), unmarried status (28.2%, p < .001), lower educational attainment (33.0%, p < .001), non-formal employment (47.2%, p < .001), and urban residence (51.2%, p < .001). Clinical factors associated with higher VF rates were ambulatory status (44.7%, p < .001), low CD4 count (35.1%, p < .001), low haemoglobin (52.2%, p < .001), advanced HIV stage III/IV (44.2%, p < .001), HIV/TB co-infection (24.3%, p < .001), and other opportunistic infections (20.5%, p = .008). Treatment-related factors associated with VF were first-line nevirapine-based regimen (27.7%, p = .009) and poor ART adherence (41.76%, p < .001). Conclusion Sociodemographic factors, advanced HIV disease, co-morbidities, poor adherence, and specific first-line ART regimens are key predictors of virological failure. Targeted, multidisciplinary interventions focusing on routine viral load monitoring, adherence support, and addressing socioeconomic barriers are essential to improve ART outcomes in East Africa.